Firms’ Location Selections and Regional Policy in the Global Economy - Ishikawa, Toshiharu; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2015)
This book offers a new understanding of how firms determine their location and what kinds of regional economic policies are needed to attract factories to a country and a region in a highly globalized economic setting. The theoretical and empirical analyses examine the influence of the transfer pricing system, corporate tax rates, and a country’s industrial structure on a firm’s decision to locate and the impact of firms’ location on regional economic activities. The theoretical analysis elucidates the importance of the above-mentioned factors in the firm’s selection of possible location. The empirical analysis uses as an example the case of a supply chain in East Asia. The empirical analysis is illustrated with the regional/spatial development experiences at the country level and city level of selected countries and cities. The analysis offers a perspective for understanding the spatial patterns of a cross-border production system.
Part I Restructuring agglomeration to spatial production network (1 Firm location and agglomeration economies: Daisuke Nakamura -- 2 Fragmentation of production process due to growth and survival competition: Toshiharu Ishikawa -- 3 Supply chain, transportation, and spatial risk: Tatsuaki Kuroda -- 4 Formation of supply chains in East Asia: Yutaka Yamada)               Part II   New location factors in global economy (5 Effects of the corporation tax rates on factory’s location through the function of the transfer price: Toshiharu Ishikawa -- 6 The Impact of transfer pricing regulations on the location decisions of MNEs: Junpei Itoh and Yoshimasa Komoriya -- 7 International comparison of corporate taxation systems: Masahiro Shinohara 8 Features of industrial and economic structure as factors for firms’ Location selections: an analysis of ASEAN countries: Mitsuhiro Hayashi) Part III　Regional economic policies in global economy (9 The role of cities in Nordic regional development policy: Lars Westin and Martin Ericksson -- 10 Regional development policies in the Philippines: from diffusion to integration: Arianne Dela Rosa Dumayas) Part IV Economic vitalization strategies of cities (11  The spatial distribution of wealth—A search for hot spots : Johan Lundberg -- 12 Establishing urbanity in a region abundance with natural resources, the case of Umeå Sweden : Lars Westin -- 13 Economic vitalization strategy of Schweinfurt, Germany: Simon Suffa -- 14 Economic vitalization strategy of Chongqing, China: Yan Sun and Yoji Taniguchi -- 15 City development in emerging economies: the case of Davao city in the Philippines: Arianne Dela Rosa Dumaya -- 16 Significance of constructing city system in regional policy: Toshiharu Ishikawa and Rickard Wall).
Keywords: Regional economics; Spatial economics; Agricultural economics; Economic policy; Regional/Spatial Science; Agricultural Economics; Economic Policy